PERFORMING PROTEST AND RECLAIMING IDENTITY: A STUDY OF SYMBOLIC VIOLENCE IN HANSDA SOWVENDRA SHEKHAR’S THE ADIVASI WILL NOT DANCE - Mahajan, Ishika; Itoo, Irshad Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The study analyzes how Adivasi women appear in Hansda Sowvendra Shekhar’s The Adivasi Will Not Dance through the examination of how caste systems and gender roles and class distinctions and governmental authority create both symbolic violence and permanent social disappearance. The study uses Pierre Bourdieu’s concept of symbolic violence together with Kimberlé Crenshaw’s intersectionality framework to examine the ways Adivasi women face identity creation and identity marketization and identity suppression through mainstream social and political systems. The paper uses the title story to show how Adivasi women become cultural tokens who institutions use to demonstrate diversity while they lose their right to participate in political decision-making and obtain justice. State-approved ceremonies and public historical remembrance and institutional communication methods use symbolic violence to create the illusion of acknowledgment which actually leads to social exclusion. The protagonist uses his dance refusal to create a radical resistance which enables him to show his power through abstaining from speech and choosing to remain silent. The study shows that national narratives make it impossible to see people who have multiple forms of marginalization. The text creates an opposing model to dominant portrayals because it allows underrepresented groups to tell their stories which leads to subaltern studies and protest literature and intersectional feminist criticism debates.